Extension of the Cayley-Hamilton theorem to continuous-time linear systems with delays - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The classical Cayley-Hamilton theorem is extended to continuous-time linear systems with delays.
Keywords: Cayley-Hamilton theorem; continuous-time; linear systems; delay; extension